PENDEKATAN PENDIDIKAN ANALISIS GENDER DALAM PERSPEKTIF AL-QUR’AN - Aas Siti Sholichah; Taryari; Nurul Hikmah (Universitas PTIQ Jakarta, 2022)
This study aims to determine the educational approach in analyzing gender. The research method uses qualitative research with a library approach. For the approach to the interpretation of the verses of the Qur'an using thematic interpretations or maudu'i interpretations. Gender analysis is a tool for analyzing data and information in uncovering the positions, roles, functions and responsibilities of women and men, identifying influencing factors and impacts that occur as a result of acculturation in life and society. In the Qur'an to be able to analyze gender, you can use an approach by knowing sex and gender. Sex is the sexes of men and women, while gender is a concept used to interpret men and women in terms of roles and functions in the order of life. The framework used in gender analysis is using the Harvard framework (role dan economic approach), Moser Analysis (Development and Gender Approach), SWOT analysis (Strengthen, Weakness, Opportunity, Threat), Longwe Framework Analysis (Empowerment Framework), and Social Relations analysis (Social welfare)